Delayed Recognition of Anti‐ NMDAR Encephalitis Mimicking Primary Psychiatric Illness: A Case Report - Bhumika Ghimire; Jagat Bhatt; Saugat Niraula; Bibek Shrestha; Arun Batsa Lamsal; Shreeram Upadhyaya (Clinical Case Reports, 2026)
ABSTRACT Anti‐N‐methyl‐D‐aspartate receptor (anti‐NMDAR) encephalitis frequently presents with prominent psychiatric symptoms, often mimicking primary psychiatric disorders and posing a significant diagnostic challenge. We report the case of a 33‐year‐old woman who presented with a 10‐day history of acute behavioral and psychiatric symptoms initially suggestive of a primary psychiatric disorder. Although initial management was directed toward psychiatric illness, the clinical course evolved with fluctuating consciousness and abnormal involuntary movements, raising suspicion of an organic neurological process. Anti‐NMDAR antibodies were detected in cerebrospinal fluid, and imaging revealed a left ovarian teratoma. The patient received intravenous methylprednisolone, intravenous immunoglobulin, and surgical excision of the teratoma, resulting in significant clinical improvement without relapse during follow‐up and was managed through a coordinated interdisciplinary approach involving psychiatry, neurology, radiology, and gynecology. This case highlights the importance of recognizing early neurological red flags in apparent psychiatric presentations and emphasizes timely interdisciplinary intervention for optimal outcomes.